Viscoplastic and Temperature Behavior of Zn–Cu–Ti Alloy Sheets: Experiments, Characterization, and Modeling - Cruchaga-Ssa., M (Elsevier Editora Ltda, 2021)
It has been experimentally observed that the Zn–Cu–Ti zinc alloy shows a strong influence of strain rate and temperature on its plastic behavior. A significant change in the material response is seen with relatively small strain rate variations or temperature. In this work, these effects are addressed through the Cazacu–Plunket–Barlat 2006 (CPB-2006) yield criterion and the Johnson–Cook hardening law. The tests were carried out over the three main directions: rolling, diagonal, and transversal. Three strain rate conditions (0.002, 0.02, and 0.2 s−1) and three temperatures (20, 60, and 80 °C) were tested. Although the experimental results exhibit a significant influence of the strain rate and temperature on stress–strain curves for all tested directions, such two variables do not practically affect the Lankford coefficients. The proposed model calibration procedure is found to describe the material responses properly under the studied conditions. © 2021 The Author(s)